PENGARUH KEWAJARAN HARGA, CITRA PERUSAHAAN TERHADAP KEPUASAN DAN LOYALITAS PENGGUNA PENERBANGAN DOMESTIK GIA DI DENPASAR - I Ketut Rahyuda; Ni Putu Cempaka Dharmadewi Atmaja (Sekolah Tinggi Ilmu Ekonomi Indonesia (STIESIA) Surabaya(STIESIA) Surabaya, 2011)
Competition of airline industry in Indonesia is not only due to globalization, but more because customers are increasingly savvy, price conscious and demanding. Garuda Indonesia as the first airline in Indonesia felt the impact of competitive domestic flight services in Indonesia. Currently the market share of Garuda Indonesia for domestic flights in Indonesia get second rank after the Lion Air who earned a market share of 30 percent. Decline in market share caused by the decline in customer satisfaction on Garuda Indonesia that caused by poor corporate image and price unfairness. Of course this is a lesson for Garuda Indonesia to increase customer satisfaction and loyalty through price fairness and corporate image. This study aims to determine the effect of price fairness and corporate image on customer satisfaction and customer loyalty of Garuda Indonesia's customer in Denpasar (Studies on Garuda Indonesia domestic flight services' customers in Denpasar). The population of this study was all Garuda Indonesia domestic flight passengers, while the sample in this study was 140 respondents using purposive sampling technique for sample determination. To answer the research problem and research hypothesis testing the analytical techniques used Structural Equation Modelling (SEM) using AMOS aid 16. The results showed that 1) the price fairness does not affect customer satisfaction, 2) Corporate image affects customer satisfaction, 3) customer satisfaction affects loyalty, 4) the prices fairness has no effect on customer loyalty, 5) corporate image does not affect on customer loyalty and 6) overall, customer satisfaction is the only construct that can affect customer loyalty.